2008
DOI: 10.1111/j.1460-9592.2008.02774.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of levobupivacaine after pediatric caudal anesthesia evaluated by transesophageal doppler

Abstract: Using transesophageal Doppler no differences in hemodynamic parameters could be detected between balanced general anesthesia with either caudal levobupivacaine or remifentanil infusion. Both techniques showed good hemodynamic stability with only minor changes from baseline over time which are unlikely to be of clinical significance except possibly in patients with preexisting cardiovascular compromise. Other studies with noninvasive monitoring in a larger population are required to better understand the conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…We observed a significant decrease in MAP (9%) after caudal block, whereas no significant decrease in MAP was seen in pediatric patients who received caudal block with or without adrenaline (11,23). Raux et al (24) reported that local anesthetics with adrenaline resulted in significant decrease in MAP (by 14%) and systemic vascular resistance (by 24%), and increase in cardiac output (by 20%) after caudal block using 1.0 mlAEkg )1 of local anesthetics with 1 : 200 000 adrenaline added.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…We observed a significant decrease in MAP (9%) after caudal block, whereas no significant decrease in MAP was seen in pediatric patients who received caudal block with or without adrenaline (11,23). Raux et al (24) reported that local anesthetics with adrenaline resulted in significant decrease in MAP (by 14%) and systemic vascular resistance (by 24%), and increase in cardiac output (by 20%) after caudal block using 1.0 mlAEkg )1 of local anesthetics with 1 : 200 000 adrenaline added.…”
Section: Discussioncontrasting
confidence: 51%
“…We observed a significant decrease in MAP (9%) after caudal block, whereas no significant decrease in MAP was seen in pediatric patients who received caudal block with or without adrenaline (11,23). Raux et al.…”
Section: Discussionmentioning
confidence: 83%
“…In the study by Bonica et al, 27 the cardiovascular effects of epinephrine injected into the peridural space appeared within 3 to 5 minutes after epidural injection of epinephrine, and peaked in 10 to 15 minutes. In a study by Galante et al, 30 a decrease in hemodynamic parameters was noted in patients receiving general anesthesia and caudal block with 0.25% levobupivacaine without epinephrine at 10 minutes after caudal injection. A patient in our current cohort sustained a medication administration error; August et al reported the effects of 88 μg/kg of epinephrine inadvertently injected into the caudal space of a 42-week postconceptual age infant.…”
Section: Discussionmentioning
confidence: 91%
“…The Author describes in Figure 1 the hemodynamic changes and the profound hypotension induced by the caudal injection of 1.6 ml·kg −1 of bupivacaine 0.125% with epinephrine. We have published on ‘ Pediatric Anesthesia ’ (2008) a research about the hemodynamic effects of levobupivacaine 0.25% after pediatric caudal anesthesia vs balanced general anesthesia evaluated by transesophageal doppler (2). In our study, epinephrine was not administered to avoid interferences on hemodynamic parameters.…”
Section: Dosage For Caudal Anesthesiamentioning
confidence: 99%